2021
DOI: 10.1017/s1355617721000801
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Cognitive Decline and its Relation to Verbal Memory and Sex in Cognitively Unimpaired Individuals from a Colombian Cohort with Autosomal-Dominant Alzheimer’s Disease

Abstract: Objective: Subjective Cognitive Decline (SCD) may be an early indicator of risk for Alzheimer’s disease (AD). Findings regarding sex differences in SCD are inconsistent. Studying sex differences in SCD within cognitively unimpaired individuals with autosomal-dominant AD (ADAD), who will develop dementia, may inform sex-related SCD variations in preclinical AD. We examined sex differences in SCD within cognitively unimpaired mutation carriers from the world’s largest ADAD kindred and sex differences in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…These findings suggest that waning cognitive abilities may have the potential to be captured early, particularly in females, with SCD+ individuals detecting subtle cognitive changes prior to objective testing. Previous studies have observed that females tend to self-report cognitive changes more than males (Martinez et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These findings suggest that waning cognitive abilities may have the potential to be captured early, particularly in females, with SCD+ individuals detecting subtle cognitive changes prior to objective testing. Previous studies have observed that females tend to self-report cognitive changes more than males (Martinez et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…These findings suggest that waning cognitive abilities may have the potential to be captured early, particularly in females, with SCD+ individuals detecting subtle cognitive changes prior to objective testing. Previous studies have observed that females tend to self-report cognitive changes more than males (Martinez et al, 2021). Combining with our findings with the increased reports in females relative to males may be indicative of either greater changes, or better perception of cognitive changes in females.…”
Section: Discussionmentioning
confidence: 98%
“…US‐based studies found that, compared to males, SMC is more strongly associated with objective memory performance among females with amnestic MCI 224 and with incident dementia among non‐demented older adults followed over 15 years 221 . Similarly, in a Colombian cohort of cognitively unimpaired individuals with autosomal dominant AD and non‐carrier family members, women had greater self‐reported SCD than men 225 . Study partner‐reported SCD was also a stronger indicator of memory decline in women versus men.…”
Section: Sex and Gender Differences In Clinical Presentations (Table 5)mentioning
confidence: 90%
“…221 Similarly, in a Colombian cohort of cognitively unimpaired individuals with autosomal dominant AD and non-carrier family members, women had greater self-reported SCD than men. 225 Study partner-reported SCD was also a stronger indicator of memory decline in women versus men.…”
Section: Sex and Gender Differences In Subjective Cognitive Decline (...mentioning
confidence: 92%
“…Studies including Latinos (i.e., with origins in Latin American countries; Jaimes et al, 2013 ) is sparse overall. Some studies investigated SCD in members of a Colombian kindred with early-onset autosomal dominant AD, where Presenilin-1 mutation carriers showed greater subjective concerns than non-carriers ( Norton et al, 2017 ), and female carriers more than males ( Martinez et al, 2021 ). Though prior research suggests protective benefits of PiL ( Wingo et al, 2020 ) and increased risk of loneliness ( Montejo et al, 2020 ) for SCD, there is a paucity of research investigating these relationships, and differences in these ratings, in ethnoracially diverse samples.…”
Section: Introductionmentioning
confidence: 99%